2003
DOI: 10.1002/art.11256
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of job loss in persons with rheumatic diseases receiving vocational rehabilitation: A randomized controlled trial

Abstract: Objective. Job loss is a major consequence of rheumatic diseases, and clinicians may refer patients to vocational rehabilitation for help. When provided after job loss, the impact of vocational rehabilitation is short term. This randomized controlled trial with 48 months of followup was undertaken to determine the efficacy of vocational rehabilitation provided to persons with rheumatic diseases while they are still employed, but at risk for job loss.Methods. A total of 242 patients with rheumatic diseases resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 24 publications
4
128
3
1
Order By: Relevance
“…Contrary to our results, the randomized controlled trial on vocational rehabilitation by Allaire et al did show a statistically significant delay and reduction of job loss (16). Like ours, their program also targeted patients at risk of job loss and included attention to job accommodation and promotion of belief in capacity for employment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results, the randomized controlled trial on vocational rehabilitation by Allaire et al did show a statistically significant delay and reduction of job loss (16). Like ours, their program also targeted patients at risk of job loss and included attention to job accommodation and promotion of belief in capacity for employment.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to the large variability of the productivity costs, it remains unclear whether, from a societal perspective, the program reduces or increases costs. Comparing our study with the study by Allaire et al (16) suggests that further research on effective vocational rehabilitation is warranted, with special attention to early detection of work problems and the collaboration between health care and vocational rehabilitation services.…”
Section: Van Den Hout Et Alsupporting
confidence: 52%
“…Research by Yelin et al found that few individuals with musculoskeletal conditions reported receiving workplace accommodations and that, with the exception of help from others, most accommodations were not associated with changes in employment rates (39). Similarly, Allaire et al found that, despite participants in their study reporting numerous work barriers, over 60% did not use any kind of workplace accommodation (5). In both these studies there were no data on availability or perceived need for different accommodations or policies among individuals with arthritis.…”
Section: Introductionmentioning
confidence: 91%
“…Studies suggest that, despite improvements in treatment for rheumatic diseases, many individuals continue to report difficulties working, have elevated absenteeism rates, and report reduced productivity (1)(2)(3)(4). In addition to the physical symptoms of the disease creating difficulties for people in remaining employed, factors like job stress, symptom unpredictability, disruptions to work because of time needed for treatment, and employment factors like a lack of job control and absence of workplace support can create barriers to working (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Intervening on work factors prior to health-related employment cessation can sustain employment and improve the performance of work-related activities and tasks among people with arthritis and rheumatological conditions [8,9]. Allaire et al demonstrated that people receiving an experimental intervention comprised of work-related barrier reduction, promotion of disability self-advocacy, and career guidance had nearly 40% lower odds of employment cessation over four years compared to the control group [8].…”
Section: Introductionmentioning
confidence: 99%